2008
DOI: 10.1162/jocn.2008.20051
|View full text |Cite
|
Sign up to set email alerts
|

Tracking the Location of Visuospatial Attention in a Contingent Capture Paradigm

Abstract: Currently, there is considerable controversy regarding the degree to which top-down control can affect attentional capture by salient events. According to the contingent capture hypothesis, attentional capture by a salient stimulus is contingent on a match between the properties of the stimulus and top-down attentional control settings. In contrast, bottom-up saliency accounts argue that the initial capture of attention is determined solely by the relative salience of the stimulus, and the effect of top-down a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
135
5

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 130 publications
(153 citation statements)
references
References 33 publications
(61 reference statements)
12
135
5
Order By: Relevance
“…The contrasting view is that stimulus features that are contingent with a current behavioural goal (e.g., redness when the target is red) have an effect on these early processing stages (Folk and Remington, 2006). Based on this position we predicted that relevance factors (e.g., distracter-target contingency) affect early ERP components simultaneously or even prior to visual saliency (e.g., luminance contrast) (Leblanc et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The contrasting view is that stimulus features that are contingent with a current behavioural goal (e.g., redness when the target is red) have an effect on these early processing stages (Folk and Remington, 2006). Based on this position we predicted that relevance factors (e.g., distracter-target contingency) affect early ERP components simultaneously or even prior to visual saliency (e.g., luminance contrast) (Leblanc et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Eimer and Kiss (2010)) found that a task-relevant, spatially uninformative cue modulated ERPs in the time-window 180-280 ms after cue onset. Using a rapid serial visual presentation task Leblanc et al (2008) found that lateral flankers sharing a critical property with the target interfered with target detection. Similar to the findings of Kiss (2008, 2010) this effect was accompanied by a modulation of the N2pc, an ERP component related to contralateral shifts of attention (Luck and Hillyard, 1994).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous ERP studies of task-set contingent attentional capture have demonstrated that the N2pc can be used to measure currently active topdown attentional control settings. During search for a specific target feature, task-set matching colour singleton cues (e.g., red singleton cues during search for red targets) triggered an N2pc, but nonmatching cues did not (e.g., red singleton cues during search for blue targets or small targets; e.g., Eimer & Kiss, 2008;Lien, Ruthruff, Goodin, & Remington, 2008;Leblanc, Prime, & Jolicoeur, 2008;Eimer, Kiss, Press, & Sauter, 2009). The presence of an N2pc to target-matching cues shows that these cues capture attention at a relatively early stage of visual-perceptual processing, while the absence of an N2pc to nonmatching cues indicates that their features fail to capture attention because they are not part of the currently active task set.…”
mentioning
confidence: 99%